TEACHING OF THE SECOND FOREIGN LANGUAGE AT SCHOOL: PROBLEMS AND SOLUTIONS - Maria Yarosh; Natalia Moskovskaya (Вестник Северо-Кавказского федерального университета)
This article is devoted to the particular qualities of the second foreign language teaching in terms of the new State Educational Standards ' introduction. The investigation deals with such problems as the second foreign language teacher's training for the purpose of his professional competence forming, and the necessity to consider by teaching some psycholinguistic factors caused by the subordinate trilingualism.